A prática do aleitamento materno exclusivo e fatores associados a sua interrupção - Marques, Mayra da Silva (2014)
Exclusive breastfeeding is recommended by the World Health Organization from birth until six months of age since breast milk is the most complete food for nutrition at this stage in life and effectively contributes to reducing illnesses and deaths in children. However, expanding the membership of the practice of exclusive breastfeeding is still a major challenge for public health in Brazil today. Consequently, knowledge of the factors associated with the discontinuation of exclusive breastfeeding is critical to the development of actions to promote and protect children’s health. Objective: To investigate the frequency of exclusive breastfeeding and associated factors its interruption among mothers of infants 0–6 months old in Santo Antônio de Jesus, Bahia. Methods: This thesis is presented in the form of an article entitled “The practice of exclusive breastfeeding and its associated factors its interruption”. This article employed the cross-sectional study design type involving 278 mothers of children under six months of age, all from the village of Santo Antônio de Jesus. Data were collected through a questionnaire administered through interviews. Results: It was found that the prevalence of exclusive breastfeeding was 39.6% in the sample studied. The interruption of associated exclusive breastfeeding was with the following variables: parity [RP=0,59; IC95% (0,44 – 0,78)], race/color maternal [RP= 1,84; IC95% (1,03 – 3,60)], an institution not supportive of breastfeeding [RP= 0,58; IC95%(0,43 – 0,77)], lack of support for breastfeeding [RP= 0,57; IC95%(0,34 – 0,95)], satisfaction with the act of breastfeeding [RP = 2,79; IC95%(1,12 – 4,03)], birth weight of the child [(RP=0,57; IC95%(0,33 – 0,98)], non-nutritive sucking habits [RP=0,55; IC95%(0,34 – 0,95)] and medical care or nursing [RP=1,68; IC95% (1,03– 3,19)]. Conclusion: The findings point to an association between the interruption of exclusive breastfeeding and factors related to sociodemographic characteristics, maternal characteristics, and the child.